Stories of change in nutrition: An overview - Gillespie, Stuart; van den Bold, Mara (Elsevier, 2017)
After a period of relative success in generating political momentum to address malnutrition, there is an increasing urgency to focus on implementation and impact on the ground. This requires better documentation of the experiences of policymakers, nutrition leaders, program managers and implementers in making decisions on what to do in real time, such as coordinating and implementing multisectoral nutrition plans in dynamic country contexts. The goal of the Stories of Change (SoC) initiative is to foster and support such experiential learning by systematically assessing and analyzing drivers of change in six high-burden contexts (Ethiopia, Zambia, Senegal, Bangladesh, Nepal and Odisha, India) that have had some success in accelerating improvements in nutrition. While recognizing context-specificity, we unpack the key pre-requisites (commitment, coherence, accountability, data, leadership, capacity and finance) that fuel and sustain progress.